Efeito dos exercícios hipopressivos sobre a distância inter-reto, função dos músculos abdominais e queixas de disfunções de assoalho pélvico em puérperas com diástase dos retos- abdominais: ensaio clínico controlado randomizado - Moreira, Sara Emmanuela (2023)
Introduction: Diastasis Recti Abdominis (DRA) is characterized by the increased distance between the rectus abdominis muscles along the linea alba. This condition can affect 100% of women in the third trimester of pregnancy and remain in 36% of women postpartum. DRA can lead to abdominal dysfunction, muscle flaccidity, and aesthetic issues. Various conservative treatments are used for permanent cases of DRA, among them hypopressive training. However, little is known about the effects of this training on postpartum women with DRA. Objectives: To examine the effect of hypopressive exercises on the distance of the rectus abdominis, abdominal function, and complaints of pelvic floor dysfunction in postpartum women with DRA. Method: A randomized controlled clinical trial in which 44 postpartum women between 45 days and 6 months postpartum with a diagnosis of DRA were included. These were randomized into two sample groups: the hypopressive group performed hypopressive exercises twice a week for 30 minutes over 12 weeks, and the control group received no intervention during the period under analysis. Before and after this period, participants from both groups were evaluated for inter-recti distance using ultrasound, discomfort related to pelvic floor dysfunction using the Pelvic Floor Bother Questionnaire, abdominal muscle function through plank and modified plank tests, and body perception was evaluated using the Body Appreciation Scale-2 (BAS-2). Results: The results found show that there were no significant differences regarding the abdominal inter-rectus distance (p>0.05). On the other hand, there was a significant improvement in abdominal muscle function in the front plank tests (p=0.014), right side plank (p= 0.026) and left (p=0.005), between groups, improved body assessment (p < 0.05) only in the hypopressive group and improved complaints of pelvic disorder dysfunction in GH (p>0.03). Conclusion: It is concluded that hypopressive training was not able to reduce DRA, but it was able to improve the function of the abdominal muscles, the body assessment of postpartum women and complaints and dysfunction of pelvic dysfunction.